Impact of climate change training intervention in savings groups - Armande Mahabi Nabami; Anaëlle Petre; Roy Mersland (Journal of International Development, 2024)
This paper investigates the impact of integrating climate change interventions in informal community-based institutions called savings groups. By integrating climate-related activities into these groups, the aim is to simultaneously strengthen the group's financial activities as well as improve knowledge and investment capacity in climate adaptation. We find that the introduction of the training increases meeting attendance rate and average loan sizes, suggesting that members can access larger sums for investment to implement the knowledge acquired during the training. We provide evidence that there are opportunities for economies of scope and for a larger positive impact on the livelihoods of the populations at the bottom of the pyramid by combining financial services offered in the savings groups and climate-related interventions.
Keywords: 650